Optimum placental thickness for Chorionic Villous sampling - Anwar, Rubina; Abidi, Taqiya S (Annals of King Edward Medical University, 2018)
One hundred and sixteen females of 10 to 13 weeks of gestation were studied by three dimensional ultrasound diagnostic technique, to obtain thickness of placenta for aspiration of chorionic villi. Previously chorionic villous sampling was done with reference to age of fetus without measuring the placental thickness. In this study adequate sampling was obtained due to prior measurement of placental thickness. The optimum placental thickness for proper chorionic villous sampling was found to be 1.25 cm.